Translation of the Alberta Continuity of Services Scale for Mental Health to a Latin American Context; [Traducción y Adaptación de la Escala de Continuidad de Servicios de Salud Mental de Alberta en Un Contexto Latinoamericano] - Rojas-Andrade, R (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2023)
Objective: Describe the process of translation, cultural adaptation to Colombia, as well as the internal consistency and construct validity of the Alberta Continuity of Services Scale for Mental Health (ACSS-MH). Methods: This instrument was subdued to the evaluation of validity of the content by experts and this was applied to a rural population in a Colombian context. Were performed tests of internal consistency and construct validity for each of the parts of the scale. Results: Under the consensus of the expert, it is made changes on some items, looking for a better adaptability of the instrument to the linguistic characteristics of Spanish, without losing sight of the evaluation objective of each one of the items on the original questionnaire. The result of the analysis of part A converged in 5 components that explain the 69.69% of the variance with 24 Items; Similarly, the analysis of part B grouped 13 items into four components, which explain the 72.02% of the variance. Discussion: This scale could be implemented to improve the provision of mental health services in Latin American contexts, where continuity of care has presented significant difficulties. © 2023 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.